Os programas de compliance na realidade do direito penal brasileiro - Gonçalves, Marcelo (2020)
Criminal law has undergone many changes due to the influence of the risk society. Once again it was proven that criminal legislation was not ready to meet some contemporary demands, including risk prevention. The purpose of the research, therefore, is to identify whether compliance programs are an instrument for preventing criminal law in a risk society, and what (or who) it is for. The idea of ​​compliance has gained a lot of traction in recent years, given the recent financial scandals, from the Enron case to "Operation Lava Jato", the theoretical study of the institute is important. The theme is part of the line of research "Social Relations and Dimensions of Power", in the issue linked to the studies of democracy in the paradigm of the contemporary Constitutional State, with an emphasis on the respective negative and positive in terms of criminal policies. The research method used was phenomenological, in which the identification of a phenomenon will be carried out, in this case, contemporary changes in the sense of the risk society, and their reflections on criminal law and the criminality of the powerful. The approach method is bibliographic, using works, jurisprudence, news and articles published in periodicals, linked to the theme. In the first chapter, following Beck, Giddens and Bauman, an attempt will be made to read contemporary times, through 05 (five) elements: fear, speed, consumption, globalization and risk; Afterwards, the reflections of the notion of risk in the contemporary sovereign nation state and its crisis will be analyzed. In the second chapter, the study will focus on the analysis of the market and the company, the criminality of the powerful, a mark of the criminal law of the risk society, and the notion of Regulatory State and Regulated Self-regulation. Finally, in the third chapter, the consequences of the risk society in criminal law will be objects of reflection, trying to understand how the notion of risk can legitimize a hegemonic discourse of domination, generating a paradox in the liberal logic of the market. Afterwards, in the face of a process of internationalization of criminal law, a study will be made of legal frameworks, national and foreign, on money laundering, corruption and compliance; in order to, in the end, analyze the structures of integrity programs within companies, in their elements required by Federal Law n.9,613/1998, by Federal Law n.12,846/2013 and by Decree n. 8,420/2015. Considering integrity programs are not included in criminal legislation, for the simple fact that, although the law uses criminal concepts, it does not create criminal types, compliance in Brazil cannot be considered as a criminal prevention instrument, and can be considered as another mechanism for maintaining the status quo, and not necessarily a change of paradigm.